The Role of Leaders in The Creation of Climate Awareness in The Community For The Realization of Environmentally Friendly and Sustainable Cities - Pieter Sahertian; Yuli Ifana Sari (Asosiasi Pengelola Publikasi Ilmiah (APPI) PT PGRI, 2024)
Climate change is one of the global challenges affecting the quality of life of communities, especially in large cities. Air pollution, declining water quality, and the impact of increasingly intense natural disasters are issues that need to be addressed immediately. In this context, city leaders have a very important role to play in raising climate awareness among the community in order to realize environmentally friendly and sustainable cities. This paper aims to explore the role of leaders in creating climate awareness and strategies that can be applied to achieve sustainable cities. The method used in this paper is a literature review with a qualitative approach. The author collects and analyzes various sources on leadership theory, climate awareness, and case study examples from cities in Indonesia that have successfully increased climate awareness under strong leadership. The results of the discussion show that city leaders can play an important role through environmentally friendly policies, public campaigns, educational programs, and encouraging community participation. Successful leaders can create sustainable cities through renewable energy policies, clean transportation, and efficient waste management. However, political, social, and economic factors and community support are the main barriers to implementing these programs. Community climate awareness can be achieved by actively engaging the community, designing sustainable policies, and building collaboration between government and the private sector. Visionary and decisive leaders are needed to ensure the success of achieving green and sustainable cities.